2018
DOI: 10.1027/1866-5888/a000203
|View full text |Cite
|
Sign up to set email alerts
|

Honesty-Humility Interacts With Context Perception in Predicting Task Performance and Organizational Citizenship Behavior

Abstract: Abstract. In this study, we investigated the interaction effects between honesty-humility and two contextual perception variables (perceptions of organizational politics and perceptions of interactional justice) on two dimensions of job performance (task performance and organizational citizenship behavior). In a multiple rater design, we dissociated the assessments of the contextual perception variables (rated by target employees), personality traits (rated by colleagues), and job performance (rated by supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
3
9
0
2
Order By: Relevance
“…By acquiring power and position, one might have created that scenario which could facilitate self-interest (Ferris, Russ, et al, 1989). POP appears as a supposedly threatening feature of every organization that encourages manipulative actions specifically to targets victims (Labrague et al, 2017), thus creating insecurities, fear to contribute positively, and the use of unethical and immoral behavior (Wendler et al, 2018). It might be obvious in the form of spreading disinformation, rumors, and blackmailing others.…”
Section: Doi: 101002/piqmentioning
confidence: 99%
See 2 more Smart Citations
“…By acquiring power and position, one might have created that scenario which could facilitate self-interest (Ferris, Russ, et al, 1989). POP appears as a supposedly threatening feature of every organization that encourages manipulative actions specifically to targets victims (Labrague et al, 2017), thus creating insecurities, fear to contribute positively, and the use of unethical and immoral behavior (Wendler et al, 2018). It might be obvious in the form of spreading disinformation, rumors, and blackmailing others.…”
Section: Doi: 101002/piqmentioning
confidence: 99%
“…They opt for ways to displace or diffuse responsibility for their behavior and try to minimize its consequences (Duffy et al, 2012). Buchanan (2008) also gave a clue that POP leads to moral disengagement in one way or another and requires its practitioners to violate important moral standards (Wendler et al, 2018). Detert et al (2008) found that moral disengagement involves intentional and premeditated actions.…”
Section: Doi: 101002/piqmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat smaller set of studies has also examined associations between H–H and OCBs (e.g., Anglim et al, 2018; Cohen, Panter, Turan, Morse, & Kim, 2014; Szabó, Czibor, Restás, & Bereczkei, 2018; Wendler, Liu, & Zettler, 2018). In general, these studies support the finding that H–H predicts incremental variance in employees’ prosocial behaviors, similar to the findings for antisocial behaviors at work.…”
Section: The Hexaco Model In Applied Contextsmentioning
confidence: 99%
“…반면, Oh 등(2014)의 연 구에서 과업수행은 인지능력과는 r = .24(p < .01), 성실성과는 r = .33(p < .05), 정직-겸손성 과는 r = .06(p > .05)으로 나타나 정직-겸손성 과 과업수행과는 유의한 상관이 관찰되지 않 았다. 정직-겸손성의 맥락수행에 대한 예측력 에 대해서는 합당한 이유가 있지만, 정직-겸손 성이 과업수행과 정적 관련성이 있다는 데에 대한 강력한 이론적 근거는 없는 실정이다(OhWendler et al, 2018).자발적 행동에 바탕을 둔 맥락수행과는 달리 과업수행은 직무기술서(job description)에 공식적으로 명시된 과업을 완수하는 것이다. 물론 정직겸손성이 높은 사람은 대체로 조 직을 위해 최선을 다하려고 하는 동기가 있 고(Wendler et al, 2018), 자신이 회사로부터 받은 보수만큼 회사에 기여해야 한다는 도 덕적 의무감을 가진다(이기범, 애쉬튼, 2013).…”
unclassified